Making University-Industry Technological Partnerships Work: a Case Study in the Brazilian Oil Innovation System - Marta Lucia Azevedo Ferreira; Ricardo Rezende Ramos (Journal of Technology Management & Innovation, 2015)
This paper approaches the research topic ‘university-industry interaction’ based on a case study in the Brazilian oil innovation system (OIS). It discourses on the management of cooperative R&D projects, by the state-owned Operator, Petrobras, involving two Brazilian universities and one medium-sized locally owned supplier firm in the scope of the Thematic Network for Integration of Science and Technology-Industry at the National Productive Process (NISTI). The NISTI is a network of scientific and technological partnerships created by the Operator to foster competitive local content and innovation in the Brazilian OIS. The case study showed the learning processes generated by the actors’ interactions were crucial to the effectiveness of the technological solutions developed by the partners. Despite the management challenges inherent in the institutional differences between academia and industry, this initiative reinforced the prominence of universities as sources of technological opportunities in science-based sectors. In addition, the adopted partnership model provided useful recommendations to the reassessment of the R&D portfolio’s formation.